European Old Masters Drawings from the Bruges Print Room. - D'Haene, Virginie; Alsteens, Stijn; Bakker, Ellen; Bleyerveld, Yvonne; Boyer, Jean-Claude; Daems, Julie; De Smet, Heleen; Dumas, Charles; Van Ootegem, Charles (Belgium : Lannoo, 2019)
Floris, Frans ; Flinck, Govaert ; Zuccari, Federico ; Callot, Jacques ; Mignard, Pierre ; Van Mieris, Jan ; van Lintelo Johan ; De Deyster, Louis
Catalogue with a selection of fifty of the most extraordinary 16th to early 18th century European drawings from the Print room of Musea Brugge.
boek